2020
DOI: 10.1038/s41598-020-71184-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of proline isomerization on potency and stability of anti-HIV antibody 10E8

Abstract: critical quality attribute for both characterization and engineering of mAbs that, based on available structures, is relevant to many potential therapeutic antibodies. Results & discussion To investigate the apparent heterogeneity of 10E8 we performed SEC under a series of conditions. As reported previously 7,8,22 , 10E8 showed elution profiles with multiple peaks. When performing SEC with a monolayer coated silica matrix (Sepax, SRT), three baseline resolved peaks (here denoted as "SEC peaks 1-3") were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Guttman et al also demonstrated that this YPP motif could be responsible for the SEC heterogeneity. 14 For the tsAb studied in the present work, the YPP motif was shown to be essential for the optimal antigen binding as various mutations within the motif led to significant loss of affinity to the target. 11 Besides, previous work demonstrated that, despite a fast sequestration of the more affine cis conformer by the antigen and a much slower binding for the trans conformer, the potency of the molecule was not impacted by the presence of two isomers due to consequent re-equilibrium of the conformers.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Guttman et al also demonstrated that this YPP motif could be responsible for the SEC heterogeneity. 14 For the tsAb studied in the present work, the YPP motif was shown to be essential for the optimal antigen binding as various mutations within the motif led to significant loss of affinity to the target. 11 Besides, previous work demonstrated that, despite a fast sequestration of the more affine cis conformer by the antigen and a much slower binding for the trans conformer, the potency of the molecule was not impacted by the presence of two isomers due to consequent re-equilibrium of the conformers.…”
Section: Introductionmentioning
confidence: 79%
“…First results revealed a conformational switching in complementarity determining regions (CDR) of the CODV arm due to a specific motif containing proline residues known to induce cis and trans isomers. More specifically, the tyrosine–proline–proline (YPP) motif of the heavy chain CDR3 (variable part targeting MPER epitope) was evidenced as playing a key role in isomerization through the interaction with a histidine residue of the light chain. Guttman et al also demonstrated that this YPP motif could be responsible for the SEC heterogeneity . For the tsAb studied in the present work, the YPP motif was shown to be essential for the optimal antigen binding as various mutations within the motif led to significant loss of affinity to the target .…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, a HIV-1 capture assay was performed ( 32 ) with three HIV-1 subtype C pseudoviruses, ZM53M.PB12, DU156.12 and CAP210.E8, known to interact with CSIR1.1( 10 ). The virus was captured with the 10E8 mAb ( 38 ) that binds gp41 and detected using different concentrations of the FITC-CSIR1.1 aptamer ranging from 0.00-0.05 mg/ml. The choice of 10E8 mAb for capture was because it binds the membrane-proximal external region of the viral glycoprotein, thus making it less likely to compete with the aptamer for binding to the envelope ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…The influence of such conformational change on protein binding kinetics is found to be comprehensive; it changes the rate of binding, the kinetic pathway, as well as the global geometry . Recent studies have also shown that proline cis – trans isomerization plays a key role in dimerization of cyclopeptides, amyloid aggregation, , and the development of antibody biotheurapeutics . These studies all highlight the effect of torsional conformational constraints on the shape-complementarity between protein partners, which is able to propagate to a protein global property change via mechanical coupling, thereby modulating binding thermodynamics and kinetics.…”
Section: Introductionmentioning
confidence: 95%